PARTISIPASI MASYARAKAT DALAM PELESTARIAN TRADISI MEAMUK-AMUKAN DI DESA ADAT PADANG BULIA KECAMATAN SUKASADA KABUPATEN BULELENG - Dewi, Ni Komang Triska Vania Cahya; Arjawa, I Gusti Putu Bagus Suka; Kamajaya, Gede (Program Studi Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Udayana, 2024)
This research describes a community participation in the preservation of a tradition that is still maintained in Padang Bulia Traditional Village, Sukasada District, Buleleng Regency. This research aims to determine the process of implementing the Meamuk-Amukan tradition and the form of community participation in the preservation of the Meamuk-Amukan tradition, as well as knowing the meaning contained in the Meamuk-Amukan tradition. The results of this study revealed that the implementation of the Meamuk-Amukan tradition was carried out after performing the pecaruan ceremony in Suter and after the community paraded the ogoh-ogoh. The form of community participation in the implementation of this tradition is in the form of money participation, property participation, energy participation, and skill participation. The Meamuk-Amukan tradition has its own meaning for the people of Padang Bulia Traditional Village, namely social meaning, religious meaning, and cultural meaning.